Pore solution alkalinity of cement paste as determined by Cold Water Extraction - Maxime Ranger; Marianne Tange Hasholt; Ricardo Antonio Barbosa (Cement, 2023)
Cold Water Extraction (CWE) is a technique used to extract the pore solution of cementitious materials and to study its alkalinity. CWE can be used on paste, mortar or concrete, and requires only standard laboratory equipment. The method is not yet standardised, so several parameters must be arbitrarily selected when conducting the test.This work investigated the influence of four parameters on the calculated alkali metal concentrations in the pore solution: the method for determining the amount of pore solution (oven-drying at 40 and 105 °C, desiccator with silica gel and solvent exchange), the size fraction of the powdered material, the leaching duration and the liquid-to-solid ratio. A comparison with values obtained by Pore Water Extraction (PWE) on two cement types emphasises and quantifies the crucial impact of the amount of pore solution on CWE results. The results suggest that some bound alkali metals may be released during CWE. A mechanism is proposed, and recommendations are made to limit any effect of this on CWE results.